Synthesis and physico-chemical properties of porphycenes - Brenner, Wolfgang; Malig, Jenny; Oelsner, Christian; Guldi, Dirk Michael; Jux, Norbert (Journal of Porphyrins and Phthalocyanines, 2012)
A new and improved synthesis for porphycenes is presented. In particular, treating pyrroles with iodine monochloride results in quantitative yields and easier work up. This key step was employed for the synthesis of different 2,7,12,17-substituted porphycenes (TPrPc, TPPc, TtBPPc). The synthetic part of this project is followed by a global analysis of the physico-chemical properties of three exemplary porphycenes, including absorption, emission, and electrochemistry. In-situ UV-vis/nIR spectroelectrochemistry was used to determine the spectral signatures of the radical anion and cation species. Temperature-dependent fluorescence lifetimes were determined under air as well as under inert atmosphere. © 2012 World Scientific Publishing Company.